The mode and timing of administrating nutritional treatment of critically ill elderly patients in intensive care units: a multicenter prospective study - Chen, Wei; Peng, Milin; Ye, Zhiwen; Ai, Yuhang; Liu, Zhiyong (Frontiers in Medicine, 2024)
Abstract Introduction: Critically ill patients are more susceptible to malnutrition due to their severe illness. Moreover, elderly patients who are critically ill lack specific nutrition recommendations, with nutritional care in the intensive care units (ICU) deplorable for the elderly. This study aims to investigate nutrition treatment and its correlation to mortality in elderly patients who are critically ill in intensive care units. Method: A multiple-center prospective cohort study was conducted in China from 128 intensive care units (ICU). A total of 1238 elderly patients were included in the study from April 26, 2017. We analyzed the nutrition characteristics of elderly patients who are critically ill, including initiated timing, route, ways of enteral nutrition (EN), feeding complications including the adverse aspects of feeding, acute gastrointestinal injury (AGI), and feeding interruption. Multivariate logistic regression analysis was used to screen out the impact of nutrition treatment on a 28-day survival prognosis of elderly patients in the ICU. Result: Our study suggested enteral nutrition in elderly during ICU admission was independent risk predictors of the 28-day mortality study in elderly patients who are critically ill Similarly, other independent risk predictors of the 28-day mortality study were, those with an OR of 2.385 (95%CI, 1.1015.168), lactate >1.5 mmol/L and ICU admission for 24 hours, those with OR, 7.004 (95%CI, 2.39520.717) and early PN delivery within 24 hours of ICU admission, and lastly those with OR, 5.401 (95%CI, 1.17524.821) with EN delivery as reference. In conclusion: This multi-center prospective study describes clinical characteristics, the mode and timing of nutrition treatment, frequency of AGI and adverse effects of nutrition in elderly ICU patients. According to this survey, ICU patients with early PN delivery, older age, faster respiratory rate, higher lactate level may experience poor prognosis.